Effects of counterfeiting on the financial performance of local generic drug manufacturers in Nairobi County, Kenya - Bosire, B. (Strathmore University, 2023)
Counterfeit drugs pose a serious threat to the credibility and finances of the pharmaceutical industry as a whole, and to drug manufacturing companies in particular. The purpose of this research was to assess the effects of counterfeit drugs on the financial performance of drug manufacturers in Kenya, focusing on the generic drug manufacturers in Nairobi County. In order to achieve the aim of the research, the study sought to meet the following specific objectives: to examine the supply chain systems of counterfeits on the financial performance of local generic drug manufacturers; to examine the effects of pricing strategy of counterfeits on the financial performance on local generic drug manufacturers; to examine the effects of the legal and institutional framework on the financial performance of local generic drug manufacturers. The study was grounded on the Theory of Reasoned Action and the Balanced Score Card. The study employed a cross sectional descriptive research design in order to paint an accurate picture of the impact counterfeit drugs have had on Kenyan generic drug manufacturing companies. There are 15 local generic drug manufacturers operating in Nairobi County registered with the Pharmacy and Poisons Board and the unit of analysis was the heads of departments in the local generic drug manufacturers. The study was based on a sample size of 75 respondents. The study used purposive random sampling to select the respondents in the study. The research adopted a well-structured questionnaire to collect data from Quality Assurance Manager, Quality Control Manager, Regulatory Affairs Manager Sales Manager and Director or C.E.O of all the local generic drug manufacturers in Nairobi County. The collected responses were analyzed in the Statistical Package for Social Sciences (SPSS Version 22.0) using descriptive and inferential techniques. The descriptive analysis findings revealed that respondents agreed with an overall mean of counterfeit drug supply chain systems of 3.86, an overall mean of pricing strategy of counterfeits 3.77, an overall mean of the legal and institutional framework of 4.01 and an overall mean of the effect of counterfeiting on the financial performance of local generic drug manufacturers of 3.72. Multiple regression analysis was run to test if counterfeiting significantly predicts the financial performance of local generic drug manufacturers. Through the consistency of the regression coefficients on the model predicators the study concludes that pricing strategy of counterfeits and the legal and institutional framework are significant factors that influence the financial performance of local generic drug manufacturers. The study recommends the collaboration between drug manufacturers and government to review the existing supply chain, improve transparency in sale and distribution of drugs in Nairobi County and access the effectiveness of the existing drug control laws to positively impact the financial performance of generic drug manufacturers in Nairobi County.
Full- text thesis